2019
DOI: 10.3389/fncel.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Acetylcholine Evoked Calcium Transients in the Developing Mouse Utricle

Abstract: Spontaneous calcium transients are present during early postnatal development in the mouse retina and cochlea, and play an important role in maturation of the sensory organs and neural circuits in the central nervous system (CNS). It is not known whether similar calcium transients occur during postnatal development in the vestibular sensory organs. Here we demonstrate spontaneous intracellular calcium transients in sensory hair cells (HCs) and supporting cells (SCs) in the murine utricular macula during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 95 publications
6
20
0
Order By: Relevance
“…Spontaneous and ACh evoked Ca 2+ transients in utricular hair cells and supporting cells have been reported previously during the first postnatal week, but ATP evoked transients were not observed (Holman et al, 2019(Holman et al, , 2020. Here, we report the presence of long-lasting Ca 2+ transients evoked by 100 µM ATP (Figure 5).…”
Section: Purinergic Signaling In Support Cells In the Utricular Maculasupporting
confidence: 85%
See 2 more Smart Citations
“…Spontaneous and ACh evoked Ca 2+ transients in utricular hair cells and supporting cells have been reported previously during the first postnatal week, but ATP evoked transients were not observed (Holman et al, 2019(Holman et al, , 2020. Here, we report the presence of long-lasting Ca 2+ transients evoked by 100 µM ATP (Figure 5).…”
Section: Purinergic Signaling In Support Cells In the Utricular Maculasupporting
confidence: 85%
“…Semi-intact vestibular preparations or apical and mid-turn sections of the cochlea from Gad2-Cre; PC-G5-tdT mice of either sex were studied from acutely dissected bony labyrinths in 4°C extracellular buffer [EB (mM): 5.8 KCl, 155 NaCl, 0.9 MgCl 2 , 1.3 CaCl 2 , 0.7 NaHPO 4 , 5,6 glucose, 10 HEPES, 1 Na pyruvate, pH 7.4; osmolality ∼308 mmol kg –1 ] ( Holman et al, 2019 ). Dissected tissue from postnatal days 4–7 (P4-P7; day of birth is P0) were transferred to a recording chamber and immobilized with a nylon harp (Warner Instrument, RC-22C), and continuously perfused with EB at room temperature (21–23°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to evoked presynaptic- and mito-Ca 2+ signals in hair cells, we also observed instances of spontaneous presynaptic- and mito-Ca 2+ signals (Example, Figure 4A–A’’’, Video 2). Numerous studies have demonstrated that mammalian hair cells have spontaneous presynaptic-Ca 2+ influx during development (Eckrich et al, 2018; Holman et al, 2019; Marcotti et al, 2003; Tritsch et al, 2007; Tritsch et al, 2010). Therefore, we predicted that similar to mammals, spontaneous presynaptic-Ca 2+ uptake may be a feature of development.…”
Section: Resultsmentioning
confidence: 99%
“…We examined vestibular neuroepithelium from the first filial generation of GAD2-IRES-Cre crossed with a dual reporter GCaMP5G-tdTomato line ( Holman et al., 2019 ). In this study, GAD2-tdTomato (GAD2-tdT) cells were observed in the EC and specific zones within vertical cristae .…”
Section: Introductionmentioning
confidence: 99%